Do we have (in)compatibilist intuitions? Surveying experimental research - Inarimori, Kiichi; Honma, Souichiro; Miyazono, Kengo (Frontiers in Psychology, 2024)
This article critically examines the experimental philosophy of free will, particularly the interplay between ordinary individuals' compatibilist and incompatibilist intuitions. It focuses on two seminal studies, Nahmias et al. (2005Nahmias et al. ( , 2006) ) and Nichols and Knobe (2007), which argue for "natural compatibilism" and "natural incompatibilism," respectively. Together, these studies reveal a complex landscape of beliefs, where participants appear to exhibit both types of intuitions. This demonstrates the need for a comprehensive understanding of folk intuitions about free will. Here, we examine error theories, which purport to explain the coexistence of apparently contradictory intuitions: the Affective Performance Error hypothesis, the "Free Will No Matter What" hypothesis, the Bypassing hypothesis, and the Intrusion hypothesis explore the cognitive errors that could shape individuals' inconsistent perceptions of free will. We then explore three possibilities regarding folk intuitions: most individuals may hold either compatibilist or incompatibilist intuitions, both simultaneously, or neither. Our aim is to deepen the understanding of the complex dynamics of intuitions about free will, and we close with suggestions for future studies in experimental philosophy.